Fatal form of immune reconstitution inflammatory syndrome (IRIS) developed post pneumonia in a solid organ transplant recipient - Hussain Hussain; Aya Fadel; Ekaterina Casmartino; John Sullivan; Amanda Fernandes; Samantha Garcia; Efrain Garcia (SpringerOpen, 2024)
Abstract Background Immune reconstitution inflammatory syndrome (IRIS) is a complex phenomenon commonly diagnosed with human immunodeficiency virus (HIV). However, rarely, IRIS can develop with other diseases outside of HIV. We are discussing a rare presentation of IRIS following a pseudomonal infection. Case presentation We present a 79-year-old Hispanic male who completed a course of cefepime for Pseudomonas aeruginosa hospital-acquired pneumonia. The patient had a 21-year history of solid organ transplant and immunosuppressive therapy, and he developed a fatal form of IRIS post-Pseudomonas aeruginosa. Conclusions IRIS may occur in any immunocompromised patient who develops an insidious onset of unexplained clinical and serological deterioration.